2015
DOI: 10.1039/c4cc09442e
|View full text |Cite
|
Sign up to set email alerts
|

Light-cleavable rapamycin dimer as an optical trigger for protein dimerization

Abstract: Rapamycin-induced protein heterodimerization of FKBP12 and FRB is one of the most commonly employed switches to conditionally control biological processes. We developed an optically activated rapamycin dimer that does not induce FKBP12-FRB dimerization until exposed to light, and applied it to control kinase, protease, and recombinase function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…[12] Computational and experimental studies confirmed that the formation of a FKBP– 4 –FKBP homodimer sterically blocked binding of FRB. Since 4 does not require the use of an engineered iFKBP or the use of an exogenous protein, such as avidin, this represents a more practical engineering approach for light-triggered dimerization.…”
Section: Optical Control Of Small Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Computational and experimental studies confirmed that the formation of a FKBP– 4 –FKBP homodimer sterically blocked binding of FRB. Since 4 does not require the use of an engineered iFKBP or the use of an exogenous protein, such as avidin, this represents a more practical engineering approach for light-triggered dimerization.…”
Section: Optical Control Of Small Moleculesmentioning
confidence: 99%
“…In order to alleviate the need for an external avidin protein while still capitalizing on the dramatic steric demand provided through recruitment of ap rotein to the caging group,asecond rapamycin molecule was linked to generate the symmetric dimer 4 (Figure 3a). [12] Computational and a) The structure of 1 is shown with the caging group in red. In this system, FAK activity was monitored in the presence of 1 with and without UV exposure.…”
Section: Optical Activation Of Rapamycin-induced Protein Dimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoprotection of dopamine, 17 histidine, 17 GABA 18 , 19 and Vemurafenib 20 has been reported. Photoprotecting groups can also be used for controlling complex biological processes, like protein dimerization 21 or gene activation 22 and gene silencing. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Several light-inducible methods based on CIP have been reported using CIP inducers caged with different photosensitive groups. These caged CIP inducers (including ABA, rapamycin, gibberellic acid, and other synthetic dimerizers) [77,[97][98][99][100][101][102][103][104][105][106][107][108] were inactive for dimerization in the caged form but can be uncaged to regenerate active inducer upon light irradiation. This photo-controlled version of CIP should be readily adaptable for light inducible epigenome editing.…”
Section: Light Inducible Epigenome Editingmentioning
confidence: 99%